Pengaruh Kompetensi, Disiplin dan Motivasi Terhadap Kinerja Guru pada SMP Negeri di Kecamatan Sukarame Kota Bandar Lampung - Jabbar, Affan Abdul; Alam, Iskandar Ali (Jurnal EMT KITA, 2023)
This study was conducted with the aim of evaluating the impact of Competency, Discipline and Motivation on the performance of teachers in State Middle Schools located in Bandar Lampung City District. Data was collected through online distribution of questionnaires via the Google Forms platform to 68 secondary schools in the Sukarame District area. Data analysis was carried out using the multiple linear regression method, by testing validity, reliability, classical assumptions, and hypotheses. The data was then processed using the Statistical Product and Service Solutions version 17 tool. Research findings show that Competency significantly and positively influences the performance of teachers at Public Middle Schools in Sukarame District. Apart from that, discipline also has a positive and significant influence on the performance of teachers at State Middle Schools in Sukarame District. Furthermore, motivation also has a positive and significant impact on the performance of teachers at State Middle Schools in Sukarame District, Bandar Lampung City.